2005
DOI: 10.1007/s00402-005-0006-4
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic anterior-inferior instability of the shoulder: arthroscopic findings and clinical correlations

Abstract: Thus we conclude that early surgical stabilization after posttraumatic anterior-inferior shoulder dislocation is necessary to prevent increasing damage within the shoulder joint.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
0
8

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(63 citation statements)
references
References 18 publications
1
54
0
8
Order By: Relevance
“…In our experience, according to other authors [7,8,13,14], during shoulder arthroscopy for instability in some patients we observed not only a detensioning of capsularlabral tissue but also an attenuation or deficiency of this tissue, that sometimes can appear very thin and inconsistent. When we are facing these conditions, a simple tensioning of this tissue may not be enough to avoid failure.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…In our experience, according to other authors [7,8,13,14], during shoulder arthroscopy for instability in some patients we observed not only a detensioning of capsularlabral tissue but also an attenuation or deficiency of this tissue, that sometimes can appear very thin and inconsistent. When we are facing these conditions, a simple tensioning of this tissue may not be enough to avoid failure.…”
Section: Discussionmentioning
confidence: 75%
“…Spatschil et al [7] noted that recurrence after primary post-traumatic shoulder dislocation causes an increasing ligamentous damage with a consequent deficiency of anatomic restraints to instability.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 The "engaging Hill-Sachs lesion" was termed by Burkhart and De Beer to describe a compression fracture of the humeral head that engages the anterior glenoid rim when the arm is placed in abduction and external rotation. Such defects are related to a greater rate of recurrent instability after arthroscopic Bankart repair alone.…”
Section: Discussionmentioning
confidence: 99%
“…Íàëè÷èå êîñòíîãî äåôèöèòà ïå-ðåäíåãî êðàÿ ñóñòàâíîé âïàäèíû âûÿâëÿåòñÿ â 20-30% ñëó÷àåâ ó ïàöèåíòîâ, ïåðåíåñøèõ ïåðâè÷íóþ òðàâìàòè-÷åñêóþ äèñëîêàöèþ [16], äî 90% ñëó÷àåâ -ó ïàöèåíòîâ ñ ðåöèäèâèðóþùèìè âûâèõàìè [17,18]. Ïîâðåaeäåíèÿ Hill-Sachs áûëè îòìå÷åíû â 31-93% ñëó÷àåâ ïåðâè÷íîãî è ïîâòîðíîãî âûâèõîâ ïëå÷à, à òàêaeå â 76% ñëó÷àåâ íåóäà÷íûõ ñòàáèëèçàöèé [19]. Êîìïüþòåðíàÿ òîìîãðà-ôèÿ ñ âîçìîaeíîñòüþ 3D-ìîäåëèðîâàíèÿ ïîçâîëÿåò ñ ìàêñèìàëüíîé òî÷íîñòüþ âåðèôèöèðîâàòü íàëè÷èå êîñò-íûõ ïîâðåaeäåíèé, èõ ðàçìåðû è ôîðìó.…”
Section: литературный обзор современных этаповunclassified
“…Òàê, ïî äàííûì àðòðîñêîïèè, áû-ëî óñòàâëåíî, ÷òî ðàñïðîñòðàíåííîñòü ïîâðåaeäåíèé Hill-Sachs äîñòèãàåò îò 47 äî 80% ïðè ïåðâè÷íîì âûâèõå è ïðèáëèaeàåòñÿ ê 100% -â ñëó÷àÿõ ðåöèäèâèðóþùåé íåñòàáèëüíîñòè [24][25][26]. Èñïîëüçîâàíèå ôîðìóëû, ïðåä-ëîaeåííîé I.K.…”
Section: литературный обзор современных этаповunclassified